divided x³ +6ײ -× by ×
Answers
Answered by
1
Step-by-step explanation:
thanks I hope you understand
Attachments:
![](https://hi-static.z-dn.net/files/d96/2339d87266e5a67b7dfca1d5b04f0815.jpg)
Answered by
0
Step-by-step explanation:
Let f(x)=x
3
−6x
2
+11x−6
and p(x)=x−2
Dividing f(x) by p(x) we get
Quotient q(x)=x
2
−4x+3 and Remainder r(x)=0
p(x)q(x)=(x−2)(x
2
−4x+3)
p(x)q(x)=x
3
−4x
2
+3x−2x
2
+8x−6
p(x)q(x)=x
3
−6x
2
+11x−6
⇒p(x)q(x)=f(x)
⇒p(x)q(x)+0=f(x)
⇒p(x)q(x)+r(x)=f(x)
Hence division algorithm verified.
solution
Attachments:
![](https://hi-static.z-dn.net/files/d3f/7083943ffed64fe895949d1b64627bf1.jpg)
Similar questions